2020
DOI: 10.4149/neo_2019_190401n284
|View full text |Cite
|
Sign up to set email alerts
|

Low pretreatment PNI correlates with worse survival in patients with stage III/IV NSCLC who received chemotherapy

Abstract: The aim of this study was to investigate the prognostic value of the prognostic nutritional index (PNI) on the long-term survival of non-small cell lung cancer (NSCLC) patients who received platinum-based chemotherapy. Data on nutritional parameters and clinicopathological characteristics [e.g., albumin, total protein, body mass index (BMI), eastern cooperative oncology group (ECOG) performance status, stage, pathology, treatment strategy] were analyzed and retrospectively correlated with overall survival (OS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Taken together, this current literature has demonstrated that a severely compromised immune system may be affected by starvation and lymphocytopenia. The NI cutoff value reported in previous studies was 40-60 for other cancer forms [18][19][20]. In our study, patients with NI < 47.5 had dramatically decreased survival when multivariate regression was corrected for other prognostic factors.…”
Section: Discussionsupporting
confidence: 42%
“…Taken together, this current literature has demonstrated that a severely compromised immune system may be affected by starvation and lymphocytopenia. The NI cutoff value reported in previous studies was 40-60 for other cancer forms [18][19][20]. In our study, patients with NI < 47.5 had dramatically decreased survival when multivariate regression was corrected for other prognostic factors.…”
Section: Discussionsupporting
confidence: 42%
“…Good nutritional status before treatment is important when undergoing chemotherapy (Chlebowski, 1985). Serum total protein and albumin levels are used as indicators of nutritional status (Sasatani, Okauchi, Ohara, Kagohashi, & Satoh, 2020;Shen et al, 2020). Several studies have used body weight and BMI as indicators of general condition in patients receiving chemotherapy (Castillo-Martínez et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The calculation of the PNI is based on the concentration of albumin and the lymphocyte count [10 × albumin (g/dL) + 0.005 × lymphocyte count (/mm 3 )]. Thus, the PNI comprehensively reflects both the nutritional and immune status of the patient and has proven reliable in predicting survival of lung cancer patients (17,18). However, the predictive value of the PNI for the QOL of late-stage lung cancer patients is unclear, so we investigated the relationships among PNI, the clinicopathological characteristics and QOL in late-stage lung cancer patients.…”
Section: Original Articlementioning
confidence: 99%